Do nationalist parties shape or follow sub‐national identities? A panel analysis on the rise of the nationalist party in the Flemish Region of Belgium, 2006–11. Issue 1 (January 2014) - Boonen, Joris; Hooghe, Marc
Abstract In this article, we examine the steep and unprecedented rise of the New Flemish Alliance (N‐VA), a Flemish nationalist party in Belgium that succeeded in gaining almost thirty per cent of the vote in a couple of years. During this period, a panel survey among 3, 025 late adolescents and young adults was conducted. Our analyses suggest that support for a sub‐nationalist ideology is far more successful in explaining a subsequent vote for the nationalist party than vice versa. In terms of supply and demand mechanisms, we find that N‐VA has managed to address a preexisting reservoir of Flemish nationalist voters (demand), rather than attributing to a development of a stronger Flemish identity among its followers (supply). We should therefore not overestimate the constructionist power of (sub‐)nationalist political elites for the development of (sub‐)nationalist identities.